Level of knowledge of FIKES students (Faculty of Health Sciences) Muhammadiyah Lamongan University about halal skincare products - Fiely, Fawwas; Handayani, Riana Prastiwi; Yuliandhari, Rully; Kusumo, Djati Wulan (Universitas Airlangga, 2024)
The majority of the religion adhered to by the population in Indonesia is Islam, where in Islam it has been ordered to all Muslims to consume, utilize and use something that is halal and also good including skincare. Skincare is a product of skin care outside the body with certain functions. However, people's knowledge of using halal skincare is still low, this is evidenced by the fact that they are still allowed to use skincare that does not have halal certification because these products are commonly used. This study aims to determine the level of knowledge of students of the Faculty of Health Sciences (FIKES) Muhammadiyah Lamongan University about halal skincare. This study used a descriptive observational research design, and the sample for this study was 2022 FIKES students, a total of 390 students. Sampling technique using purposive sampling. The instrument used was a closed questionnaire in the form of Google form. The results showed that the knowledge level of FIKES students about halal skincare was in the good category of 47.69%, the sufficient category was 46.16%, the less category was 6.15%. It can be concluded that the knowledge level of FIKES students at Muhammadiyah Lamongan University about halal skincare is in the good category.